Service Performance Guarantees for Public Utilities and Beyond : An Innovation with Potential to Attract Investors to Emerging Markets - Ramachandran, Vijay; Gelb, Alan; Buehler, Martin Reto (International Finance Corporation, Washington, DC, 2019)
Emerging market countries require substantial foreign investment for development, economic growth,and poverty alleviation. There are multiple challenges to attracting this investment, however, ranging from political and economic instability to corruption, poor security, and small market size. An additional challenge is inadequate delivery of key services like electricity and other utilities that private firms and investors rely on. Service performance guarantees are a promising approach to addressing this issue. These guarantees enable firms to purchase protection against poor or insufficient service delivery, and they may work particularly well in industrial or export processing zones by ensuring that shortfalls in service delivery are measured, reported, and addressed in a timely manner.